2019
DOI: 10.1267/ahc.18045
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Mapping of Bcl9 Using Two Antibodies that Recognize Different Epitopes Is Useful to Characterize Juvenile Development of Hepatocellular Carcinoma in Myanmar

Abstract: B-cell lymphoma 9 (Bcl9) is the core component of Wnt/β-catenin signaling and overexpressed in nuclei of various tumors, including hepatocellular carcinoma (HCC). However, the extent of Bcl9 expression relative to HCC differentiation stage and its functional aspects are poorly understood. In this study, we examined the expression pattern of Bcl9 immunohistochemically, using two anti-Bcl9 antibodies; one was a conventional polyclonal-antibody (anti-Bcl9ABC) against amino acid no.800–900 of human-Bcl9, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…1 a). With this antibody, we previously revealed that the loss of cytoplasmic Bcl9 was associated with the progression of histopathological grade of HCC in Myanmar [ 41 ]. In agreement with that findings, cytoplasmic Bcl9 expression was noted in the normal liver tissue, but was decreased in well differentiated HCC and almost negative in moderately and poorly differentiated HCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a). With this antibody, we previously revealed that the loss of cytoplasmic Bcl9 was associated with the progression of histopathological grade of HCC in Myanmar [ 41 ]. In agreement with that findings, cytoplasmic Bcl9 expression was noted in the normal liver tissue, but was decreased in well differentiated HCC and almost negative in moderately and poorly differentiated HCC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that aberrant expression or nuclear localization of Pygo2 or Bcl9 correlates with poor HCC prognosis [ 18 , 19 , 39 , 58 ]. Our group had also demonstrated the expression of Bcl9 in the cytoplasm even in the normal liver tissue, while the expression is significantly decreased during the progression of histopathological grade and also in juvenile HCC in Myanmar [ 41 ]. The gradual loss of cytoplasmic Bcl9 along with the progression of HCC suggests the association of Pygo2 not only in poorly differentiated HCC but also in most of Myanmar HCC by inducing nuclear translocation of Bcl9 followed by activation of Wnt/β-catenin signaling.…”
Section: Introductionmentioning
confidence: 99%